Acute ischemic stroke secondary to cardiac embolus of a 'foreign body' material after a redo sternotomy for mitral valve replacement: A case report. Issue 2 (April 2019) - Fitzgerald, Seán; Rizvi, Asim; Dai, Daying; Williamson, Eric E; Lanzino, Giuseppe; Doyle, Karen M; Kallmes, David F; Brinjikji, Waleed
Summary: Cardiac surgery has been shown to be associated with increased risk of acute ischemic stroke. This report presents a case of a successful mechanical embolectomy procedure to treat a patient for an acute ischemic stroke, which was caused by the cardiac embolization of a 'foreign body' containing debris following a redo sternotomy procedure for mitral valve replacement and tricuspid valve annuloplasty.